New Ideologies on Scarlett Whitening Advertisement: Interpreting Symbols of New Masculinity - Ariella, Jihan; Putrib, Citra Fransisca Indah Lestari Dano; Usu, Novi R; Talani, Noval Sufriyanto (Tuturlogi: Journal of Southeast Asian Communication, 2023)
Masculinity came from the construction of maleness, which means it is made and not born, neither inherent nor natural. The evidence of different masculinity shows in Scarlett Whitening's advertisement. Song Joong Ki, a man and South Korean actor who became the brand ambassador of a skincare brand in Indonesia, shows masculinity in South Korea. The symbols displayed in Scarlett Whitening's advertisement "Get Ready to Meet Song Joong Ki's New Love" were analyzed using a qualitative approach and a tradition of communications, namely semiotics traditions. The theory used Roland Barthes's semiotics, which explores the representation of masculinity symbols. The research results showed that Song Joong Ki had used Scarlett Whitening skincare to support his appearance. In this advertisement, Song Joong Ki still wears typical male accessories. He also features a romantic act, such as giving gifts to the woman he loves. These symbols represent the ideology of new masculinity, which has the potential to break down the understandings of masculinity that have been constructed by society.